2018
DOI: 10.1016/j.jelechem.2018.03.041
|View full text |Cite
|
Sign up to set email alerts
|

High capacity surface route discharge at the potassium-O2 electrode

Abstract: Discharge by a surface route at the cathode of an aprotic metal-O2 battery typically results in surface passivation by the non-conducting oxide product. This leads to low capacity and early cell death. Here we investigate the cathode discharge reaction in the potassium-O2 battery and demonstrate that discharge by a surface route is not limited to growth of thin (<10 nm) metal oxide layers. Electrochemical analysis and in situ Raman confirmed that the product of the cathode reaction is a combination of KO2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…At the end of cycling the membrane in battery charging/discharging tests, the cathodes are rinsed in DME, and a post-mortem SEM and EDX of the PPy side is performed. [27] In the characterization studies reported in this paper, the discharge potentials largely remain outside of this window (in charge/discharge data in Figure 4) and therefore KO 2 is the expected discharge product. This indicates that KO 2 is formed at the cathode/ separator interface and not just at the air-facing side of the cathode.…”
Section: Kà O 2 Batteries With Different Types Of Cathode Configuratimentioning
confidence: 77%
See 1 more Smart Citation
“…At the end of cycling the membrane in battery charging/discharging tests, the cathodes are rinsed in DME, and a post-mortem SEM and EDX of the PPy side is performed. [27] In the characterization studies reported in this paper, the discharge potentials largely remain outside of this window (in charge/discharge data in Figure 4) and therefore KO 2 is the expected discharge product. This indicates that KO 2 is formed at the cathode/ separator interface and not just at the air-facing side of the cathode.…”
Section: Kà O 2 Batteries With Different Types Of Cathode Configuratimentioning
confidence: 77%
“…It should also be noted that recent reports indicate the formation of K 2 O 2 at low potentials (~2.25 V vs K/ K + ) on gold electrodes in acetonitrile. [27] In the characterization studies reported in this paper, the discharge potentials largely remain outside of this window (in charge/discharge data in Figure 4) and therefore KO 2 is the expected discharge product. Previous studies have shown that the average crystal size of KO 2 decreases with increasing discharge rate.…”
Section: Under Argonmentioning
confidence: 77%
“…Nonetheless, the reaction pathways can also be tuned similarly. For example, Bruce's group found that the surface route can achieve high discharge capacity in K–O 2 battery, which was entirely different from that in Li–O 2 and Na–O 2 systems . Although the mechanism remains obscure, it may provide some helpful information in developing high‐performance K–O 2 battery.…”
Section: Strategies For a Stable Aprotic Electrolytementioning
confidence: 99%
“…Due to the kinetic preference for superoxide and enhanced stability of KO 2 with respect to its peroxide, the potassium‐oxygen battery has demonstrated selectivity for KO 2 formation. Only in the case of a gold electrode has potassium peroxide been reported, indicating that pursuing electrodes with higher catalytic activity may result in the formation of undesired potassium peroxide …”
Section: Potassium‐oxygen Batteriesmentioning
confidence: 99%
“…Only in the case of ag olde lectrode has potassium peroxide been reported, indicating that pursuing electrodes with higher catalytic activity may result in the formation of undesiredp otassium peroxide. [40] The formation and morphology of KO 2 has been investigated as af unctiono fa ppliedc urrent and solvent. The discharge current or growth rate of KO 2 can affect the crystallite size distribution ( Figure 8).…”
Section: Discharge Productmentioning
confidence: 99%